IMPORTANCE OF CONSERVATION OF THE BRAZILIAN CERRADO (CIPEEX, 2022)
THE CERRADO IS AN IMPORTANT BIOME, NOT ONLY FOR THE DIVERSITY OF PLANT SPECIES THAT IT SHELTERS, BUT ALSO FOR THE ECOLOGICAL ROLE IT PLAYS IN THE REGION. AMONG THE PROBLEMS OF ANTHROPOGENIC ORIGIN FACED BY THE CERRADO, DEFORESTATION HAS CONTRIBUTED TO THE LOSS OF NATIVE VEGETATION AND, CONSEQUENTLY, BIODIVERSITY. TO REVERSE THIS TREND, SOME CONSERVATION MEASURES CAN BE USED, SUCH AS THE ESTABLISHMENT OF PROTECTED AREAS AND SUSTAINABLE LAND MANAGEMENT. PURPOSE: THE PRESENT WORK AIMED TO EXPLORE THE IMPORTANCE OF THE CERRADO AS A BRAZILIAN BIOME AND POSSIBLE MEASURES TO BE TAKEN FOR ITS CONSERVATION. MATERIAL AND METHOD: THE TECHNIQUE USED FOR THE CONSTRUCTION OF THIS RESEARCH RESIDED IN THE BIBLIOGRAPHIC RESEARCH IN PRIMARY SOURCES AND IN REPOSITORIES, USING THE COMPARATIVE AND STATISTICAL METHODOLOGY, THROUGH THE PARAMETRIC INFERENTIAL TESTS. STUDIES ON THE PLANT DYNAMICS OF SHRUBS AND TREES WERE CARRIED OUT IN THE CERRADO COMPLEX IN SCOPUS, WEB OF SCIENCE AND SCIELO INDEXES. IN ADDITION, A SEARCH WAS CARRIED OUT ON THE GOOGLE SCHOLAR INDEX FOR DISSERTATIONS AND THESES WITH THE SAME SUBJECT. THE SEARCH TERMS USED WERE: 'VEGETATION DYNAMICS' AND 'CERRADO' AND 'CERRADO PHYSIOGNOMY€™, FOR EXAMPLE, 'DENSE CERRADO' AND 'TREE' OR 'SHRUB'. RESULTS: THE BRAZILIAN CERRADO BIOME IS COMPOSED OF A HIGHLY HETEROGENEOUS TROPICAL SAVANNA AND IS ONE OF THE HOT SPOTS OF GLOBAL BIODIVERSITY. THIS BIOME RECEIVES LITTLE ATTENTION FROM SOCIETY AND THE GOVERNMENT FOR CONSERVATION PURPOSES AND LACKS SPECIFIC PUBLIC POLICIES THAT EFFECT ITS CONSERVATION. CONCLUSIONS: CERRADO PLANT BIODIVERSITY IS HIGH, WHICH MEANS THAT THERE IS A WIDE VARIETY OF PLANTS IN THE REGION. THIS DIVERSITY PROVIDES A RICHER ENVIRONMENT FOR WILDLIFE AS IT OFFERS MORE FOOD AND SHELTER FOR THE ANIMALS. HOWEVER, THE LOSS OF BIODIVERSITY CAN CAUSE PROBLEMS FOR THE SPECIES THAT DEPEND ON THIS VEGETATION, SUCH AS A DECREASE IN THE AMOUNT OF AVAILABLE FOOD AND SHELTER FROM PREDATORS. STUDIES HAVE HIGHLIGHTED THE IMPORTANCE OF CONSERVING THIS IMPORTANT BRAZILIAN BIOME, BECAUSE IN ADDITION TO THE ASPECTS, THE CERRADO IS ALSO AN IMPORTANT NATURAL RESOURCE FOR THE LOCAL POPULATION. UNFORTUNATELY, IS BEING INCREASINGLY DESTROYED BY HUMAN ACTIVITIES, SUCH AS DEFORESTATION FOR AGRICULTURE AND LIVESTOCK, WHICH REPRESENT THE MAIN NEGATIVE IMPACTS TO ITS CONSERVATION. TO IMPROVE THE UNDERSTANDING OF THE SUBJECT, A MAP OF THE CERRADO REGION IN BRAZIL WAS MADE, EMPHASIZING THE MAIN PLANT CHARACTERISTICS AND THE MAIN NEGATIVE IMPACTS TO ITS CONSERVATION.
Keywords: CERRADO; CONSERVATION; Phytophysiognomy; Biodiversity